Vacuum-Enhanced Optical Nonlinearities with Disordered Molecular Photoswitches - Herrera-Urbina, F (American Physical Society, 2019)
It is well known that nonlinear optical signals such as cross-phase modulation can be coherently enhanced in multilevel atomic gases under conditions of electromagnetically induced transparency, but analogous results in solids are challenging to obtain due to natural energetic disorder. We propose a solid-state cavity QED scheme to enable cross-phase modulation between two arbitrarily weak classical fields in the optical domain, using a highly disordered intracavity medium composed of organic molecular photoswitches. Even in the presence of strong energetic and orientational disorder, the unique spectral properties of organic photoswitches can be used to enhance the desired nonlinearity under conditions of vacuum-induced transparency, enabling cross-phase modulation signals that surpass the detection limit imposed by absorption losses. Possible applications of the scheme include integrated all-optical switching with low photon numbers. © 2019 American Physical Society.